ANALISIS CITY BRANDING DALAM PENGEMBANGAN DESTINASI PARIWISATA KABUPATEN JAYAPURA - Bawanti, Ari (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
Jayapura district is a district located in the province of Papua. Unidirectional on the vision and mission of "New Jayapura district" makes the Jayapura district currently holds the role as the major developments in the polar region in particular of Jayapura. But the Jayapura district has not had the appropriate brand status in the field of tourism. In the framework of marketing and competition in the world of tourism, of course not wrong if Jayapura district also boasts a unique identity that expresses the uniqueness of Jayapura district itself. This study aims to determine views or perceptions of market participants travel (tourists) on the formation of a destination image Jayapura district and identify the elements of the establishment of a brand that is suitable for city branding prepare for Jayapura district. The method used is the method mix between quantitative and qualitative methods by taking a sample of 30 respondents rating, which then disedkripsikan perception of market participants travel to the image of Jayapura District as a destination and the elements of what is appropriate to draw up branding Jayapura city. The results showed that the image of Jayapura district as a tourism destiinasi is unique, comfortable, Lake Sentani, culture, youth and diversity of nature. Keywords: City branding, Jayapura district, the image of the destination.